Exploring Al-Faruqi’s Perspective on Christian Ethics: A Balanced Critique - Mohd, Siti Hadija (Universitas Islam Negeri Sumatera Utara, 2025)
This article evaluates Ismail Raji al-Faruqi's book Christian Ethics: A Historical and Systematic Analysis of Its Dominant Ideas. The study looks at Al-Faruqi’s approach to comparative religion, especially his concept of “Epochè” and his critique of exclusivity in Jewish and Christian ethics. Using library-based research and deductive analysis, the article explores how Al-Faruqi highlights universal moral values and deals with the challenges of interfaith dialogue. The findings show that while Al-Faruqi stresses ethics as a shared human concern, he also confirms Islam’s comprehensive ethical framework. This study shows how Al-Faruqi’s work contributes to better understanding among different religious communities and offers methods for improving interreligious dialogue and cooperation.